Enhanced renal clearance and impact on vancomycin pharmacokinetic parameters in patients with hemorrhagic stroke - Kathryn A. Morbitzer; Denise H. Rhoney; Kelly A. Dehne; J. Dedrick Jordan (Journal of Intensive Care, 2019)
Abstract Background The majority of patients with hemorrhagic stroke experience enhanced renal clearance or augmented renal clearance (ARC). The purpose of this study was to determine the impact of enhanced renal clearance or ARC on vancomycin pharmacokinetic (PK) parameters. Methods This was a post hoc analysis of a prospective study of adult patients with aneurysmal subarachnoid hemorrhage (aSAH) or intracerebral hemorrhage (ICH) admitted to the neurosciences intensive care unit who received vancomycin. Creatinine clearance (CrCl) was measured and also estimated using the Cockcroft-Gault equation. Predicted PK parameters were compared with calculated PK parameters using serum peak and trough concentrations. Results Seventeen hemorrhagic stroke patients met inclusion criteria. All patients experienced enhanced renal clearance on the day that the vancomycin concentrations were obtained, and 12 patients (71%) experienced ARC. The mean calculated elimination rate constant was significantly higher than the predicted value (0.141 ± 0.02 vs. 0.087 ± 0.01 h−1; p = 0.004) and the mean calculated half-life was significantly lower than the predicted half-life (6.5 ± 0.9 vs. 8.7 ± 0.6 h; p = 0.03). Conclusions Patients with hemorrhagic stroke and enhanced renal clearance displayed PK alterations favoring an increased elimination of vancomycin than expected. This may result in underexposure to vancomycin, leading to treatment failure.